2017
DOI: 10.1002/bit.26261
|View full text |Cite
|
Sign up to set email alerts
|

Light dilution via wavelength management for efficient high‐density photobioreactors

Abstract: The spectral distribution of light influences microalgae productivity; however, development of photobioreactors has proceeded largely without regard to spectral optimization. Here, we use monochromatic light to quantify the joint influence of path length, culture density, light intensity, and wavelength on productivity and efficiency in Synechococcus elongatus. The productivity of green light was ∼4× that of red at the highest levels of culture density, depth, and light intensity. This performance is attribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 52 publications
3
30
1
Order By: Relevance
“…However, in terms of light quality, it has been shown that different wavelengths can enhance the sustainability of cyanobacteria cultures according to the target of production (Pagels et al, 2019). For instance, multiple studies reported that red light (650 nm) and blue light could promote the production of EPS or accelerate metabolic paths in cyanobacteria from genera Nostoc, Synechocystis and Synechococcus (Bland & Angenent, 2016;Han et al, 2017a;Han et al, 2017b;Ooms et al, 2017), and the microalgae Chlorella (Atta et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, in terms of light quality, it has been shown that different wavelengths can enhance the sustainability of cyanobacteria cultures according to the target of production (Pagels et al, 2019). For instance, multiple studies reported that red light (650 nm) and blue light could promote the production of EPS or accelerate metabolic paths in cyanobacteria from genera Nostoc, Synechocystis and Synechococcus (Bland & Angenent, 2016;Han et al, 2017a;Han et al, 2017b;Ooms et al, 2017), and the microalgae Chlorella (Atta et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies sought to dilute the supplied light intensity by optimizing the light spectra distribution. These attempts were encouraged by the integration of light emitting diodes (LEDs) within indoor PBRs ( Ooms et al, 2017 ). Tailoring light wavelength spectrum affords improved growth conditions stability and reproducibility and has been shown to lead to concrete achievements in biomass productivity and ultimately in the accumulation of useful products.…”
Section: Introductionmentioning
confidence: 99%
“…Among hydrogels formed with 150 mM Ca 2+ , the first harvested layer achieved the greatest individual layer productivity in all cases, with the maximum of 1.0 g DW m −2 d −1 achieved in hydrogels subjected to a 3‐day harvest period. This productivity is high for S. elongatus , comparable to that of suspension cultures supplemented with elevated carbon concentrations and in similar illumination conditions (Modiri et al, ; Ooms et al, ; Silva et al, ). Overall, the biomass productivities of all harvested layers suggests a material cost of biomass production of a few tens of cents per kilograms of dry mass per year (alginate‐dominant), which is comparable with that estimated for PSBR production (Podola et al, ).…”
Section: Resultsmentioning
confidence: 63%